Smart Tendonhamm Touch / Lily Marliza Jamian, Norhafiza Awang … [et al.] - Jamian, Lily Marliza; Awang, Norhafiza; Che Mamat, Nurul Awanis; Abu Bakar, Rosni; Mohd Shuhimi, Tun Sholehah (2018)
Assessment of the patient is a key component of Medical Practitioner Practice. It include patient history, general appearance, physical examination and vital signs. The physical assessment involve with our product are neurological assessment for deep tendon reflex testing and eye assessment. After initial observation combine with working experience towards usual TendonHammer in Hospital setting, the team had chosen a product that we believe can contribute tot he Medical Practitioner community. Deep tendon reflex testing incorporates an assessment ofthe function and interplay of both sensory and motor pathways. The product is "Smart TendonHamm Touch". Our product known as Smart tendon hammer is a multifunction tendonhammer that have improved features which can facilitate in assessment of the patient. Our product is inspired from a humble tendon hammer that might seem like an outdated medical device, but its role in diagnosing disease is still as important as ever. It also most important tool in narrowing down the differential diagnosis.